Good citizenship in America - Ricci, David M. (Cambridge University Press, 2004)
In order to describe an American civic ideal for those who enjoy membership in the state and the obligations entailed, this study traces its development in American history. Starting from the republicanism of pre-1865, the book follows the widening of the franchise following post-1865 economic development. It characterizes the twentieth century by the increase and subsequent decline of consumerism, and by the development, in later years, of the "economic conscience". The volume's analysis of civic trends in America highlights many of the inherent ideals of American life.